Job Satisfaction: Motivation, Empowerment, Compensation, and Transformational Leadership Impact: Kepuasan Kerja: Dampak Motivasi, Pemberdayaan Karyawan, Kompensasi, dan Kepemimpinan Transformasional. - Beti Aprilia Pratiwi; Sriyono Djemain (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to investigate the influence of work motivation, employee empowerment, compensation, and transformational leadership on job satisfaction among employees. Employing a quantitative research design with hypothesis testing, a sample of 75 respondents from various professional backgrounds participated in the study using the accidental sampling technique. Data collected through Likert-scale questionnaires were analyzed using the SmartPLS 3.0 software. The results demonstrate that work motivation, employee empowerment, compensation, and transformational leadership are all positively and significantly related to job satisfaction. These findings highlight the importance of these factors in enhancing job satisfaction, which has implications for organizations seeking to improve employee well-being and productivity. Highlights: Positive Relationships: Work motivation, employee empowerment, and compensation positively impact job satisfaction. Leadership Influence: Transformational leadership significantly contributes to higher job satisfaction. Organizational Implications: Findings have practical implications for enhancing employee well-being and productivity. Keywords: Job Satisfaction, Work Motivation, Employee Empowerment, Compensation, Transformational Leadership